Degradasi Identitas Komunitas Samin Studi Kasus di Kudus Jawa Tengah - Rosyid, Moh (DEMOS: Journal of Demography, Ethnography and Social Transformation, 2021)
This article describes the changes in lifestyle Samin community in Kudus Central Java. Data collection by interview, observation, and literature was analyzed using a qualitative descriptive approach. Result, Samin is Javanese ethnic community the originally driven by Ki Samin Surosentiko against invaders in Blora, Central Java. Its existence extends to city Kudus, Central Java until now. Samin community in Kudus changes in lifestyle. The result (1) follow a lifestyle now and (2) become urban worker, and (3) some are no longer farmers. This is due to fulfilling a lifestyle consequently experienced degradation quantity and quality. Triggered by don't understand the teachings Samin, don't identity Samin.